Political Identity in Discourse The Voices of New Zealand Voters - Woodhams, Jay M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"Giving voters their voice, Woodhams' interview-based study offers a richly inflected portrayal of political identity in New Zealand. At once fluid and stable, these voices nuance the meanings of political tenets such as egalitarianism and its converse, the 'tall poppy'. Woodhams' approach through critical realism is a refreshing counterpoint to the hyper-constructivism of some contemporary discourse analysis." - Allan Bell, Professor of Language and Communication, Auckland University of Technology, New Zealand This book takes an innovative view of language and politics, charting the terrain of political identities and discourses in New Zealand through detailed linguistic analysis of interactions with its voters. The author first sets out the geographical and sociopolitical context, examining how the constraints of a small and isolated country interact with widespread social values such as egalitarianism. He then delves into the multiple nature of identities and explores how Kiwis form their political selves through informal talk with others and in engagement with their physical and discursive surroundings. In doing so, the author provides an in-depth exploration of New Zealand political culture, identity and discourse, and sheds light on how we use language to become political people. This book will be of interest to linguists, political scientists and sociologists working with discourse analysis. Jay M. Woodhams teaches academic literacy at the Australian National University, Canberra, and is a Research Associate of the Language in the Workplace Project, Victoria University of Wellington, New Zealand. He has published on populist political discourse in New Zealand and has looked at language use in the workplace and parliamentary contexts. His areas of interest include interactional sociolinguistics, pragmatics, cognitive linguistics and theories of discourse.
Chapter 1. Introduction -- Chapter 2. Political landscapes: Physical, social and historical -- Chapter 3. Kiwi egalitarianism and tall poppies -- Chapter 4. A liberal bubble: Discourse at the local level -- Chapter 5. Stances of self and other -- Chapter 6. Multiple stances, multiple identities -- Chapter 7. Conclusion.
Keywords: Linguistics -- Methodology; Sociolinguistics; Communication in politics; Philosophy of mind; Self; Culture; Australasia; Research Methods in Language and Linguistics; Sociolinguistics; Political Communication; Philosophy of the Self; Australasian Culture